MODELING OF QUASISTATIONARY MODES OF DIRECT-CURRENT MOTOR UNDER PULSATING SUPPLY USING DYNAMIC MATHEMATICAL MODEL - Irina Romanenko; Maksim Danilov (Вестник Северо-Кавказского федерального университета)
The algorithm of quasistationary modes modeling of DC motor feeding on pulsating voltage was introduced. The algorithm bases on verifying calculation amendmented by dynamic mathematical DC motor model for taking into account pulsating supply voltage. The results of speed and mechanical performance modeling with dynamic mathematical motor model and without it were presented.